Bariatric Surgery for Severe Obesity - Biswas, PK; Mahmood, I (TAJ: Journal of Teachers Association, 2009)
Obesity is a chronic, relapsing, debilitating, life-long disease. It is defined as a body mass index (BMI) of 30 kg/m2 or more, affects 1.7 billion people world-wide. It is a complex, multifactorial chronic disease. Its medical treatment is not effective, and costly. Obesity is the harbinger of many diseases that affects many organ system of the body. Bariatric surgery is long lasting, cost-effective, and reduces co-morbidity efficiently. The procedures are, adjustable gastric banding, Rou x-en-Y gastric bypass, biliopancreatic diversion with duodenal switch, and vertical banded gastroplasty, of which Roux-en-Y gastric bypass is the gold standard. Indications are BMI >40 kg/m2 or BMI >35 kg/m2 with co-morbidity. Lifelong follow-up is required for appropriate weight loss. Bariatric surgery should be considered as a main stream of surgical specialty and should be practiced in our context. TAJ 2009; 22(1): 319-323